The Loss of Soil and Fertilizer in Khao Mahachai, Nakhon Si Thammarat Province - Markphan, Wattananarong; Seangrakung , Araya; Prayod, Kasidit (Burapha Science Journal, 2026)
Soil loss, fertilizer loss, and loss of value of fertilizer in the soil with planting 3 types: fruits orchard, Mixed Garden, and rubber plantation at an average slope of 35 percent, Found that the mixed garden area has the most soil loss at 0.68 tons / rai / year. And the loss of fertilizer in the soil was found Fruit orchards lose the most fertilizer at 179.66 kg/ rai / year. Followed by rubber plantations and mixed Garden lost 166.64 and 155.97 kg of fertilizer / rai / year, respectively. The most lost value of fertilizer in the soil was Fruits orchards, which was 5,587.40 baht / rai /r year. Followed by the rubber plantation and the equation is 5,486.70 and 5,109.00 baht / rai / year